Risk Factors for Postoperative Fibrinogen Deficiency after Surgical Removal of Intracranial Tumors. - Naili Wei; Yanfei Jia; Xiu Wang; Yinian Zhang; Guoqiang Yuan; Baotian Zhao; Yao Wang; Kai Zhang; Xinding Zhang; Yawen Pan; Jianguo Zhang (PLoS ONE, 2015)
Higher levels of fibrinogen, a critical element in hemostasis, are associated with increased postoperative survival rates, especially for patients with massive operative blood loss. Fibrinogen deficiency after surgical management of intracranial tumors may result in postoperative intracranial bleeding and severely worsen patient outcomes. However, no previous studies have systematically identified factors associated with postoperative fibrinogen deficiency. In this study, we retrospectively analyzed data from patients who underwent surgical removal of intracranial tumors in Beijing Tiantan Hospital date from 1/1/2013to12/31/2013. The present study found that patients with postoperative fibrinogen deficiency experienced more operative blood loss and a higher rate of postoperative intracranial hematoma, and they were given more blood transfusions, more plasma transfusions, and were administered larger doses of hemocoagulase compared with patients without postoperative fibrinogen deficiency. Likewise, patients with postoperative fibrinogen deficiency had poorer extended Glasgow Outcome Scale (GOSe), longer hospital stays, and greater hospital expenses than patients without postoperative fibrinogen deficiency. Further, we assessed a comprehensive set of risk factors associated with postoperative fibrinogen deficiency via multiple linear regression. We found that body mass index (BMI), the occurrence of postoperative intracranial hematoma, and administration of hemocoagulasewere positively associated with preoperative-to-postoperative plasma fibrinogen consumption; presenting with a malignant tumor was negatively associated with fibrinogen consumption. Contrary to what might be expected, intraoperative blood loss, the need for blood transfusion, and the need for plasma transfusion were not associated with plasma fibrinogen consumption. Considering our findings together, we concluded that postoperative fibrinogen deficiency is closely associated with postoperative bleeding and poor outcomes and merits careful attention. Practitioners should monitor plasma fibrinogen levels in patients with risk factors for postoperative fibrinogen deficiency. In addition, postoperative fibrinogen deficiency should be remediated as soon as possible to reduce postoperative bleeding, especially when postoperative bleeding is confirmed.